30.7k views
2 votes
Given f(x) = 3x - 1 and g(x) = 2x - 3, for which value of x does g(x) = f(2)?

User Hepifish
by
5.9k points

2 Answers

4 votes

Answer:

x = 4.

Explanation:

f(2) = 3(2) - 1 = 5.

So 2x - 3 = 5

2x = 5 + 3

x = 8/2 = 4 (answer).

User Alex Chesters
by
4.9k points
4 votes

Answer:

g(x) =f(2) when x=4

Explanation:

First step is to find f(2)

f(2) is when x=2

f(2) = 3(2) -1

f(2) = 6-1

f(2) = 5

We want to find x when g(x) =5

g(x) = 2x-3

5 = 2x-3

Add 3 to each side

5+3 = 2x-3+3

8 = 2x

Divide each side by 2

8/2 = 2x/2

4 = x

User Shan Plourde
by
7.1k points